End‐to‐End Continuous Manufacturing of Pharmaceuticals: Integrated Synthesis, Purification, and Final Dosage Formation1. Issue 47 (2nd October 2013) - Mascia, Salvatore; Heider, Patrick L.; Zhang, Haitao; Lakerveld, Richard; Benyahia, Brahim; Barton, Paul I.; Braatz, Richard D.; Cooney, Charles L.; Evans, James M. B.; Jamison, Timothy F.; Jensen, Klavs F.; Myerson, Allan S.; et al.
<x xml:space="preserve">Abstract</x> A series of tubes: The continuous manufacture of a finished drug product starting from chemical intermediates is reported. The continuous pilot‐scale plant used a novel route that incorporated many advantages of continuous‐flow processes to produce active pharmaceutical ingredients and the drug product in one integrated system.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>